El turismo cultural religioso como una alternativa para el desarrollo económico de la parroquia La Matriz del cantón Latacunga. - Sarango Estrella, Cinthya Kruskaya (2022)
The present research work is to establish a Cultural Route of the Churches that helps us as a tool for the economic development of La Matriz parish, Latacunga city, which involves all the providers of tourist services that exist in Latacunga city. The research work´s general goal was to: "establish the importance of cultural tourism in the economic development of La Matriz parish in Latacunga canton", the research process was based exclusively Cultural Religious Tourism to develop the cultural route of the churches, as a research method was managed: scientific, inductive, deductive, theoretical and observation, with a documentary design, field, the techniques for the collection of information were, the observation, the survey applied to tourists, for the inventory of the churches, in addition, the guide established by the MINTUR and the lifting of tourist attractions in Ecuador and the manual for generating tourist routes and itineraries were used. The results of the research show that the objectives set in the research were met and the design of the cultural route of the churches will serve for the cultural diffusion of La Matriz parish, Latacunga canton and in this way to attract tourists which will help to the economic development of the city.